(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
The number of works on historical themes in Uzbek literature, which is included in the treasury of world literature, is growing.In the near future, Uzbek prose will change its character, embracing reality in all its complexity and reflecting it in its own way, in its direction and contradictions